On the episodic excursions of massive protostars in the Hertzsprung–Russell diagram. Issue 2 (10th January 2019) - Meyer, D M-A; Haemmerlé, L; Vorobyov, E I
ABSTRACT: Massive protostars grow and evolve under the effect of rapid accretion of circumstellar gas and dust, falling at high rates (≥10 −4 −$10^{-3}\, \rm M_{\odot }\, \rm yr^{-1}$ ). This mass infall has been shown, both numerically and observationally, to be episodically interspersed by accretion of dense gaseous clumps migrating through the circumstellar disc to the protostellar surface, causing sudden accretion and luminous bursts. Using numerical gravitoradiation-hydrodynamics and stellar evolution calculations, we demonstrate that, in addition to the known bloating of massive protostars, variable episodic accretion further influences their evolutionary tracks of massive young stellar objects (MYSOs). For each accretion-driven flare, they experience rapid excursions towards more luminous, but colder regions of the Hertzsprung–Russell diagram. During these excursions, which can occur up to the end of the pre-main-sequence evolution, the photosphere of massive protostars can episodically release much less energetic photons and MYSOs surreptitiously adopt the same spectral type as evolved massive (supergiants) stars. Each of these evolutionary loop brings the young high-mass stars close to the forbidden Hayashi region and might make their surrounding H ii  regions occasionally fainter, before they recover their quiescent, pre-burst surface properties. We interpret such cold, intermittent pre-main-sequence stellar evolutionary excursions, and the dipping variability of H ii regions as the signature of the presence of a fragmenting circumstellar accretion disc surrounding the MYSOs. We conjecture that this mechanism might equivalently affect young stars in the intermediate-mass regime.